Changing Law from Barrier to Facilitator of Opioid Overdose Prevention. Issue 1 (16th April 2013) - Davis, Corey; Webb, Damika; Burris, Scott
Abstract : Opioid overdose is the leading cause of accidental injury death in the United States, taking the lives of over 16, 000 Americans every year. Many of those deaths are preventable through the timely provision of naloxone, a drug that reliably and effectively reverses opioid overdose. However, that drug is often not available where and when it is needed, due in large part to laws that pre‐date the overdose epidemic. Preliminary evidence suggests that amending those laws to encourage the prescription and use of naloxone will reduce opioid overdose deaths, and a number of states have done so in the past several years. Since legal amendments designed to facilitate naloxone access have no documented negative effects, can be implemented at little or no cost, and have the potential to save both lives and resources, states that have not passed them may benefit from doing so.